1986
DOI: 10.1103/physrevb.33.4686
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of chaos in a Josephson junction by the Melnikov-function technique

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…For small values of A and n /V 0 , the e(q, s) can be treated as perturbation such that the perturbed solution reads q(s) ¼ q 0 (s) þ q 1 (s) with the zero-order heteroclinic solution q 0 (s) and the first-order "chaotic solution" q 1 (s) in the forms 18,25 q 0 ¼ 2arctan½sinhðs þ t 0 Þ;…”
Section: Classically Chaotic and Regular Regionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For small values of A and n /V 0 , the e(q, s) can be treated as perturbation such that the perturbed solution reads q(s) ¼ q 0 (s) þ q 1 (s) with the zero-order heteroclinic solution q 0 (s) and the first-order "chaotic solution" q 1 (s) in the forms 18,25 q 0 ¼ 2arctan½sinhðs þ t 0 Þ;…”
Section: Classically Chaotic and Regular Regionsmentioning
confidence: 99%
“…4 Subsequently, many theoretical and experimental works demonstrated that classical chaos enhanced quantum tunneling rate drastically 2,3,14 even without a barrier to tunnel through. 2,3 Particularly, in the absence of collisions and dephasing effects, a particle in a static and tilted lattice is localized in a certain range, due to the celebrated Bloch oscillations, 15 while the presence of a periodically varying ramp results in chaos [16][17][18] and delocalization. 7,19 In addition, there exist other situations, where both the quantum localization and delocalization may be independent of the classical chaos.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fixing the parameters F ¼ 0:25, b ¼ 2, c ¼ 1, we plot the chaotic regions on the V 0 À g 0 plane as in Fig. 2, where the region above the curve is the Melnikov chaotic region in which the evolution of the atomic number density and energy density have the properties of Smale-horseshoe chaos [32], and the system is generally unstable in this region. Given the chaotic region, we can let the system be in the chaotic state or not, by adjusting the external and internal potential strengths.…”
Section: Article In Pressmentioning
confidence: 99%
“…The method of Melnikov· analysis has been used to predict the lowest threshold for chaos in this system. 11 We carry out detailed investigations regarding the possible routes to chaos, the nature of the chaotic state, etc. in this model.…”
Section: The Equation Of Motion Ror Tbe Josephson Juuction With Nonlimentioning
confidence: 99%